SISTEM DETEKSI KERUSAKAN PADA SISTEM OPERASI MENGGUNAKAN METODE TF-IDF DAN COSINE SIMILARITY - Aa Zezen Zaenal Abidin; Andi Sukmadinata (JURNAL ILMIAH INFORMATIKA, 2020)
System damage to the operating system, errors in the operating system, with damage to software and hardware. The detection system is expected to be more flexible than an ordinary expert system, because in an ordinary expert system the consultation is guided while in the detection system using the text similarity method, the user can express the consultation using free expressions on the user consultation menu by using the user consultation text. The system uses the Term Frequency-Inverse Document Frequency method. Once the operating system malfunction query is filled in to the system, the query preprocessing is carried out and the text document is in the database, dedicating the weight of the relationship of a word to the document. After doing the word weighting process, then do the document crunching against the query using the Cosine Similarity method. A collection of text that has been classified in the database which is used as the basis of knowledge and the text consulted as a query, obtained the operating system damage detection system with two categories, namely software and hardware damage. The system is able to create consulted crashes by checking the similarity of the query text and knowledge base. The results of the evaluation using a matrix that shows an accuracy value of 70 percent, the next research in error detection using text similarity is expected to increase the reliability of the system with even greater assessments.